Vida u obra de Petrarca : Volumen I: Lectura del Sectretum - Rico, Francisco (North Carolina studies in the Romance languages and literatures. Essays ;, 2019)
With Vida u Obra de Petrarca, Dr. Francisco Rico questions whether the traditional biography of Petrarch is a product of the real life of the author, or from the critical understanding of his work. In this volume, he analyzes the environment and periodization of the Secretum, relocating its date of publication. It has long been assumed that the Secretum--composed of three dialogues in which "Augustine," in the presence of "Truth" tries to persuade "Francis" to seek spiritual perfection--reflects a spiritual crisis on the part of the author. This is the supposition that Dr. Rico calls into question. This comprehensive, Spanish-language study opens the way for a more realistic interpretation of both the works and motivations of Petrarch.